American Society for Composites 2017 2017
DOI: 10.12783/asc2017/15406
|View full text |Cite
|
Sign up to set email alerts
|

Verification and Validation Process for Progressive Damage and Failure Analysis Methods in the NASA Advanced Composites Consortium

Abstract: The Advanced Composites Consortium is a US Government/Industry partnership supporting technologies to enable timeline and cost reduction in the development of certified composite aerospace structures. A key component of the consortium's approach is the development and validation of improved progressive damage and failure analysis methods for composite structures. These methods will enable increased use of simulations in design trade studies and detailed design development, and thereby enable more targeted phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…4b) and the damage sensitive interface (i.e. the continuous plies interface of ply drop 1 in front of the pre-insert) is mode I loaded, thus its mesh convergence trend is consistent with the mode I numerical cohesive zone length as derived by a DCB model and the requirement of at least two to three elements existing in the cohesive zone [21,23,26,29,[32][33][34][35][36][37]. A DCB model with a very fine mesh (0.025 mm) was run following the procedures detailed in Refs.…”
Section: Mesh Sizesupporting
confidence: 72%
See 1 more Smart Citation
“…4b) and the damage sensitive interface (i.e. the continuous plies interface of ply drop 1 in front of the pre-insert) is mode I loaded, thus its mesh convergence trend is consistent with the mode I numerical cohesive zone length as derived by a DCB model and the requirement of at least two to three elements existing in the cohesive zone [21,23,26,29,[32][33][34][35][36][37]. A DCB model with a very fine mesh (0.025 mm) was run following the procedures detailed in Refs.…”
Section: Mesh Sizesupporting
confidence: 72%
“…[30,31]. There exists discrepancy in the literature regarding the cohesive strength pair [21,23,26,29,[32][33][34][35][36][37] and the TTC enhancement factor [28,38,39]. The reason why [60 MPa, 90 MPa] is used here as the baseline cohesive strength pair is simply because that it has been proved to give satisfactory predictions for many of the previous IM7/8552 laminate models [21,23,26,31,40,41].…”
Section: Interlaminar Failurementioning
confidence: 99%
“…Bertolini et al [7][8] showed that this can be used both for symmetrical and skewed buckling. Recently, NASA performed seven-point bending tests as part of the Advanced Composite Consortium (ACC) program [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The three-point bending test, in which out-of-plane deformation is applied to a specimen with a skin and a co-bonded or co-cured doubler, is representative of the opening mode of a stringer flange disbond [1][2] that results from a combination of the high deflection of the skin and the mismatch in flexural stiffness of the skin and stringer. A similar type of damage has also been investigated using a seven-point bending (7PB) test, which adds the complex interaction of the buckling deformation of the skin [3][4][5]. The 7PB test consists of a single-stringer specimen supported at five points and loaded at two points such that the out-of-plane deformation of the skin is similar to a half-wave section of a postbuckled multi-stringer panel.…”
Section: Introductionmentioning
confidence: 99%
“…In all of these tests, debonding of the skin-stringer is dominated by mode I loading, representing the location where the deflection due to the buckling wave is at its maximum. However, research on skin-stringer separation indicates that a possible combined mode II + III failure can also be a critical mode of failure due to the twisting of the skin at the inflection point, located in between two buckling halfwaves [5,9]. Inflection points can be critical locations, for example, in structures with a tapered stringer flange termination, where a relatively low bending stiffness mismatch between the skin and stringer flange reduces the likelihood of separation in mode I.…”
Section: Introductionmentioning
confidence: 99%